Unraveling the role of ecosystem development in the shaping of soil bacterial communities - S. Borin; F. Mapelli; E. Rolli; R. Marasco; S. Ciccazzo; B. Scaglia; F. Adani; D. Daffonchio; L. Brusetti (2013)
Microbial primary succession and plant biocoenosis establishment are key events in land reclamation, nevertheless the underlying mechanisms driving the succession are still poorly understood. Aim of the work was hence to determine the role of environmental factors and ecosystem development in shaping soil microbiota. The forefronts of receding glaciers are natural laboratories where to study microbial diversity in relation to geochemical factors and ecosystem development stage. Chronosequences can be identified on glacier moraines, where the increasing distance from the glacier edge corresponds to the increase of time of permanence out of ice, soil structuring and ecosystem development. We studied a first site on the moraines of the Lobuche glacier (Mount Everest area, Nepal), identifying several niches characterized by a different level of biotic colonization, from a bare mineral substrate to complex biological soil crust. Bacterial phylogenetic and functional diversity was studied by DNA-fingerprinting methods and a high variability was observed, demonstrating that the presence of spatially isolated microhabitats in soil matrices can strongly influence data interpretation. We then focused on a second site on the moraines of the Midtre Lovéenbren glacier (Svalbard Islands, Norway) where a chronosequence was previously characterised (Hodkinson et al. 2003). The sequence was composed by 7 sites subjected to a primary succession process, exposed to the terrestrial habitat since 5 to 2000 years, thus not isolated by distance but by the age of ecosystem evolution, distinguished by increasing levels of nutrient availability, soil fertility and plant colonization. Together with environmental factors, plant cover and diversity have been demonstrated to strongly influence the structure of soil microbiota (Berg & Smalla 2009). To have the possibility to consider separately the role of plants and the role of soil development in the primary bacterial succession, we identified a vascular plant, namely Saxifraga ...